The performance of upper arm circumference for age in diagnosing severe acute malnutrition in children aged 6 to 59 months in South Kivu, Eastern Democratic Republic of Congo: Lwiro Cohort - Gaylord Ngaboyeka; Armand Mulume; Emmanuel Lurhangire; Anouk Neven; Lydia Zigabe; Serge Balolebwami; Pacifique Mwene-Batu; Michelle Dramaix; Philippe Donnen; Ghislain Bisimwa (BMC Public Health)
Abstract Background The studies on the use and performance of the Mid-Upper Arm Circumference for age (MUACZ) for the diagnosis of severe acute malnutrition (SAM) are still rare. Our study aimed to analyze the performance of MUACZ for diagnosis of SAM in South Kivu, eastern DR Congo. Methods We analyzed a database of children admitted from 1987 to 2008 for management of SAM in the east of the DRC. Anthropometric indicators (z-score) were calculated and classified according to the standards of the World Health Organization (WHO). To evaluate the performance of MUACZ using the combination of weight-for-height (WHZ) and Mid-Upper Arm Circumference (MUAC) as the reference, we calculated sensitivity, specificity, positive and negative predictive values (PPV and NPV) overall. Subsequently, we stratified the results by age category, presence or absence of stunting, and presence or absence of edema. Results Of the 9969 children aged 6 to 59 months selected, 30.2% had nutritional edema, 70.1% had stunting. Of all cases of SAM (identified by at least one of the WHZ, MUAC, or MUACZ indicators), MUACZ alone identified 85% of them, surpassing other criteria such as MUAC (58%) and WHZ (45%). The MUACZ-WHZ combination identified 97%, surpassing the MUAC-WHZ combination (76%). In the presence of edema, MUACZ-WHZ identified 99%, while MUAC-WHZ identified only 72%. The proportions of SAM cases diagnosed by MUACZ increased according to age groups, with rates of 73% (6–11 months), 85% (12–23 months) and 91% (24–59 months). In the presence of stunting, the detection rates were 58% for MUAC alone, 44% for WHZ alone, 89% for MUACZ alone, 67% for the MUAC-WHZ combination, and 98% for the MUACZ-WHZ combination. MUACZ had a sensitivity of 80.7% (79.9–81.5), a specificity of 92.3% (91.8–92.8), a PPV of 71.5% (70.7–72.4) with a prior prevalence was 19,3% defined by the reference, and an NPV of 95.2% (94.8–95.7). Sensitivity increased in the presence of edema [90.1% (88.9–91.1)], stunting [84.7% (83.8–85.5)] and in children over 12 months [83.6% (82.2–84.9)]. Conclusion The MUACZ was performing well in our region. In a context of high prevalence of stunting and kwashiorkor, MUACZ appears to be a more reliable indicator than MUAC alone. Moreover, the MUACZ-WHZ combination also seems to outperform the MUAC-WHZ combination. These results highlight the MUACZ potential, as well as its combination with WHZ, in enhancing screening of SAM in similar contexts.